Animation Effectiveness for E-Learning with Progressive Web App Approach: a Narrative Review - Wijaya, Hadi; Alayham Abbas, Rabab; ., . (International Journal of Engineering and Technology, 2018)
Understanding the content of a subject is the most fundamental thing a student should do to acquire the skills and knowledge. Animation is one way to provide an interesting way of learning. ALETRIA project is the reason to support the students for use animation methods that developed in novel e-learning concept. As a first step, the study of animation and e-learning development became the basis of this narrative literature. Terms of search that used in this paper is animation for learning, engagement and learnerâ€™s motivation. E-learning development with Progressive Web Apps (PWAs) were excluded from the search terms. 29 papers were selected for review as they are relevant to the criteria. The combined results of these papers recommend that there is reason to confident that the development of e-learning animations with the PWA approach might be effective to use.Â Â